Frequência de casos de COVID-19 e sintomas gripais em pacientes internados em um hospital psiquiátrico no Brasil: um estudo observacional - Azorli, Laura Alqueja (Universidade Federal de São Carlos, 2023)
Introduction: The COVID-19 pandemic has reflected on the mental health of the world's population and individuals with mental disorders are even more susceptible to the coronavirus infection. Objective: To identify the frequency of positive cases of COVID-19 among patients admitted to a psychiatric hospital in Brazil between the years 2020 and 2022. Method: This is a quantitative observational study carried out using secondary data. A total of 6,698 patients were admitted and/or admitted to a Psychiatric Hospital in Brazil and of these, 1,201 were tested for COVID-19 between June 2020 and September 2022. Patients with flu symptoms or according to an institutional protocol for possible contact with suspicious patients. Results: The patients tested were mostly male, 65.8% (n = 654), with a mean age of 43.98 (15.34) years. The frequency of positive cases for COVID-19 among patients who had flu-like illness was 34.2%. Of the total of 6,698 patients hospitalized and/or admitted during the study period, there was an average frequency of 5.1% of positive cases for COVID-19. Of the patients who tested positive for COVID-19, 35.7% were symptomatic. Conclusion: Understanding how the spread among psychiatric patients makes it possible to create strategies to minimize the spread of COVID-19 in these sectors. In addition, psychiatric hospitals are important centers that need attention in public health emergencies.
Frequency of COVID-19 cases and flu-like symptoms in patients admitted to a psychiatric hospital in Brazil: an observational study
Keywords: Covid-19; Hospitais Psiquiátricos; Prevalência; Coronavírus; CIENCIAS DA SAUDE